Spatio-Temporal Analysis of Reported Trachoma Cases in Kano State, Nigeria (2013-2019) - Abubakar Isyaku Ismail; Amina Hayat Saleh; Tukur Abdulkadir (CV Media Inti Teknologi, 2025)
Trachoma is caused as a result of chronic infection of the conjunctiva by chlamydia trachomatis and is the world’s leading infectious cause of blindness, more especially in developing countries due to poverty, overcrowding, poor sanitation, poor water supply, unimproved latrines and unhygienic management of kept animals all leads to the disease. The study analyzed the reported cases of trachoma in Kano State. Hospital records for seven years (2013 – 2019) were obtained from three specialist eye hospitals and from the neglected Tropical disease unit of the Department of Public Health and Disease Control Ministry of Health Kano State. To show spatio-temporal distribution of the disease, coordinate of wards in the state were generated and imported into Arc GIS environment for mapping. Hotspot and cold spot analysis were used to determine the risk areas of trachoma prevalence. Spatial distributions of trachoma in the state were shown using choropleth maps; and prevalence rate at local government levels were depicted. The findings revealed high prevalence of the disease in non-metropolitan local government areas (LGAs) which include Gabasawa, Shanono, Kura, Tudun wada with a prevalence of 231,000 – 301,000 cases per 100,000 people per year. The trend analysis of trachoma shows endemicity throughout the years in the state with a very high prevalence rate in 2017, and decline in 2018 and 2019. This study recommendations that the implementation of the WHO SAFE strategies, surgery for Trichiasis antibiotics for disease, facial cleanliness and environmental improvement.